FAKTOR RISIKO LINGKUNGAN PADA KEJADIAN ASMA DI WILAYAH KERJA PUSKESMAS MANGKANG KOTA SEMARANG - Anamika Labitta; Budiyono Budiyono; Mursid Rahardjo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Semarang’s Asthma cases have increasing in from 5040 to 5711 cases in 2013. Based on number of cases, which 177 cases on 2014 and 133 case on 2015, the Asthma prevalence of Puskesmas Mangkang is 1,5℅. Asthma is affected by the family asthma’s occurrence and the air particulate pollution, such as PM10 and PM2.5. The air pollutant particulates are identified from House condition. This research aims to identify the correlation between environmental risk factors and asthma occurrences at Puskesmas Mangkang’s working area. The research methodology used observational analytic with case control study design. The sample size are 37 respondents in each case and control groups. There are using univariate and bivariate analysis with Chi Square test. The average temperature is 31 degree Celsius, 65% air humidity, and PM10 concentration 585µg/m3. The result shows from 8 independent variables there are 2 variables those correlate to asthma case, those are indoor air humidity (p-value= 0,048; OR= 3,96; 95% CI= 1,140-13,756) and furry pets ownership (p-value=0,036; OR= 2,70; 95% CI= 1,056-6,941). Finally, Indoor air humidity and furry pets ownership are factors that correlate to asthma’s occurrences in Puskesmas Mangkang’s working area.